Mini-Review: Impaired Axonal Transport and Glaucoma. (3rd March 2016) - Fahy, Eamonn T.; Chrysostomou, Vicki; Crowston, Jonathan G.
Abstract: Glaucoma is increasingly recognized as a neurodegenerative disorder, characterized by the accelerated loss of retinal ganglion cells (RGCs) and their axons. Impaired axonal transport has been implicated as a pathogenic mechanism in a number of neurodegenerative diseases, including glaucoma. The long RGC axon, with its high metabolic demand and crucial role in conveying neurotrophic signals, relies heavily on intact axonal transport. In this mini review, we consider the evidence for transport disruption along RGCs in association with glaucoma and other intraocular pressure models. We give a brief overview of the axonal transport process and the methods by which it is assessed. Spatial and temporal patterns of axonal transport disruption are considered as well as the reversibility of these changes. Biomechanical, metabolic and cytoskeletal insults may underlie the development of axonal transport deficits, and there are multiple perspectives on the impact that transport disruption has on the RGC. Eliciting the role of impaired axonal transport in glaucoma pathogenesis may uncover novel therapeutic targets for protecting the optic nerve and preventing vision loss in glaucoma.